Physical Properties of Electrode Materials of Rechargeable Lithium Ion Batteries via DFT Calculations - Zeinab Saeedi Pour; Jaafar Jalilian; Seiyed Hamid Reza Shojaei (Progress in Physics of Applied Materials)
We performed a density functional theory (DFT) study on Li2VO2F to assess its electronic structure. All calculations were conducted employing the plane wave pseudopotentials basis set. Electronic structure of Li2VO2F was calculated in the framework of the Hubbard U density functional theory (DFT+U) method. The geometry of the unit cell was optimized in triclinic and monoclinic phases. The effect of adding the Hubbard parameter on the band structure as well as the partial density of states were investigated and the contribution of different atoms in the total density of states was investigated separately. Hubbard parameter added the electron-electron interaction in the calculations, which has led to an increase in the bandgap value and more accurate results compared to the existing experimental results. It was observed that the monoclinic phase exhibits a smaller gap bandwidth than the triclinic phase. Also the calculated band structure indicates the presence of an indirect gap in both phases of this compound.